Aggressive driving behavior: road rage incidents in Athens from the clinical forensic point of view - Dimitrios Kouzos; Konstantinos Katsos; Ioanna Anastopoulou; Christoforos Kolentinis; Nikolaos D. Goutas; Dimitrios G. Vlachodimitropoulos; Konstantinos Moraitis; Chara A. Spiliopoulou; Emmanouil I. Sakelliadis (Egyptian Journal of Forensic Sciences)
Abstract Background Aggressive driving behavior may lead to interpersonal violence. The Athens Metropolitan area has over four million inhabitants. Public transportation has improved over the last decades, mainly due to the work performed before the 2004 Olympic Games but is still lacking in the coverage of the Attica region with fixed track transportation. Thus, traffic in Athens is usually heavy during the day, a fact that combined with limited parking spaces available, acts as fuel to aggressive driving behaviors. For this retrospective study, data from forensic clinical examinations performed at our department by the authors were reviewed. More specifically, cases examined from January 1st, 2012, to September 30rd, 2021, all concerning allegations for road rage were included, totally 177 cases. The data obtained was analyzed by utilizing SPSS Statistics. Results Most victims and perpetrators were drivers of their vehicles. In most cases (85.3%), perpetrators acted alone. 80.2% of victims reported that the incident was triggered by a minor conflict. Perpetrators used mostly just their hands and feet, or even their head as a blunt force instrument to inflict injuries (72.3%). Hammers, crowbars, and brass knuckles were used in 12.4% of cases, while in 9.6% the vehicle was used to overrun the victim. In 2.8% of cases, perpetrators attempted to strangulate the victims, while in 1.7% they used a sharp force instrument. In 9.6% of cases, victims did not sustain any visible external injury. 18.1% of victims sustained just a single injury, while in 72.3% multiple injuries were observed. 69.5% victims sustained merely external injuries, while in 20.2% at least one internal organ injury was sustained. The predominant injury site was by far the head-neck region. In more than one third of the road rage incidents, the injuries could be characterized as grievous. Conclusions Most people involved were male motorists. Females are rarely victims of road traffic violence, and even more rarely act as perpetrators. Commonest injury site was the head-neck region, with second commonest the upper extremities.